Recycled aggregate seawater–sea sand concrete and its durability after immersion in seawater. (15th April 2023) - Lu, Zhongyu; Liu, Genghao; Wu, Yifan; Dai, Meiling; Jiang, Mingchao; Xie, Jianhe
Abstract: Recycled coarse aggregate (RCA), seawater, and sea sand are sustainable and environmentally friendly materials that may be combined to make a new green building material. In this study, mineral admixtures were added to improve the properties of recycled aggregate–seawater–sea sand concrete (RASSC). The specimens were prepared with different replacement ratios of RCA, fly ash (FA), and silica fume (SF). The design compressive strength was set at C40 and optimized by orthogonal design. The durability of RASSC with the optimal mix proportion after immersion in artificial seawater at room temperature was studied in terms of axial compression performance, and flexural properties. The results showed that the compressive strength of RASSC with mineral admixtures could reach 47.8 MPa and that SF had the greatest influence, followed by RCA and FA. The continuous hydration and pozzolanic reaction of cement, FA and SF in the RASSC resulted in an increase in the axial compression performance and flexural properties at the initial stage of immersion. As the immersion time increased, chloride ions reacted with the cement product and formed Friedel salts, sulfate ions reacted with calcium hydroxide to form ettringite, gypsum and salt crystals, and the RASSC was more brittle with a poor ductility, resulting in the flexural failure mode changed from interface transition zone of recycled aggregate to recycled aggregate failure, fracture interface characterization results provided the evidence. The theory of plasticity was still applicable to RASSC, and the stress–strain relations was proposed. Highlights: The performance of a new green building material with RCA, seawater, and sea sand was studied. Recycled aggregate–seawater–sea sand concrete was more brittle after seawater immersion. The flexural failure mode changed from ITZ to recycled aggregate as immersion increased. The theory of plasticity in structural design process to the application still applicable for RASSC.